Frailty, Pitavastatin, and Major Adverse Cardiovascular Events Among People With HIV - Kristine M. Erlandson, MD, MS; Ariela R. Orkaby, MD; Triin Umbleja, MSc; Heather J. Ribaudo, PhD; Todd T. Brown, MD, PhD; Markella V. Zanni, MD; Marissa R. Diggs, AB; Sarah M. Chu, MSN; Kathleen V. Fitch, MSN; Carl J. Fichtenbaum, MD; Carlos Malvestutto, MD, MPH; Judith A. Aberg, MD; et al. (JACC: Advances)
Background: People with HIV (PWH) are at increased risk for atherosclerotic cardiovascular diseases (ASCVDs) and geriatric syndromes, including frailty. REPRIEVE (Randomized Trial to Prevent Vascular Events in HIV) demonstrated a 36% reduction in major adverse cardiovascular events (MACE) with pitavastatin vs placebo but the role of statins for ASCVD prevention among frail PWH is not known. Objectives: The purpose of this study was to evaluate whether frailty is associated with MACE and whether pitavastatin prevents MACE regardless of frailty. Methods: We conducted a post hoc analysis of the REPRIEVE trial, a randomized, blinded trial of pitavastatin 4 mg vs placebo. Participants included PWH without ASCVD, aged 40 to 75 years. Frailty was measured with a 32-item frailty index. Cox proportional hazards models were used to estimate cause-specific hazard of MACE by frailty status. Pitavastatin effect modification by frailty status was assessed via interaction with treatment. Results: Of 7769 REPRIEVE participants, 7,740 (>99%) had sufficient data to calculate frailty index. Median age was 50 years (Q1, Q3: 45, 55), 67% were nonfrail, 29% prefrail, and 4% frail at baseline; median follow-up was 5.6 years. Adjusted for age, sex, ASCVD risk score, and treatment group, MACE hazard increased with frailty (P < 0.0001): HR: 1.76 (95% CI: 1.35-2.30) among prefrail, and 2.14 (95% CI: 1.33-3.45) among frail compared to nonfrail. There was no evidence that pitavastatin effect differed by frailty status (P = 0.44). Conclusions: Frailty was associated with markedly higher hazard of MACE. Though frailty did not appear to modify the protective effects of pitavastatin seen in the primary trial, the efficacy in frail PWH remains uncertain due to the limited number of frail individuals.